Évaluation Du Niveau D’efficacité Technique Des Systèmes De Production A Base De Maïs Au Bénin - Mamam, Toléba Séidou; Gauthier, Biaou; Afio, Zannou; Aliou, Saïdou (European Scientific Journal, ESJ, 2016)
This study estimates the technical efficiency of a sample of 411 maïzicoles farms in the main production areas in Benin. The study proposed an evaluation of the technical performance of these farms and identified factors of inefficiency by using the model of the production stochastic frontier Cobb-Douglas to assess the levels of efficiencies of systems production involved in the first step. A truncated regression was used in the second stage in order to establish a relationship between the indices of technical efficiency and some exogenous variables or attributes. The results of the first step shows that the index of technical efficiency varies from 37.37 to 96.22% for all systems, and that of the average technical efficiency is 80.35%. The maximum value of technical efficiency of at least 92.75% obtained shows that there are very efficient producers in the study sample as being close to the production frontier. These producers who obtain such a high productivity can be referred to generally improve the productivity of maize production systems in Benin. The results of the second stage indicate that the variables such as access to fertilizers and herbicides, the use of animal traction and tractor, technical guidance and access to credit influence significantly (p <0.05 to p <0.001) the technical efficiency of maize farms surveyed.